Penerapan Explicit Instruction pada Mata Kuliah Desain Grafis dan Animasi - Rachmawati Rachma (Universitas Muhammadiyah Sidoarjo, 2017)
In maximizing learning objectives before learning a teacher must recognize aspects or characteristics of learners. Thus the educator must be able to prepare adequate resources and learning media and learning model in accordance with the level of intellectual development of learners. In the preliminary study the obstacles encountered were the fourth semester students who took the course of Graphic Design and Animation Offering B as much as 40% had not been able to use the computer, then used the Explicit Instruction learning model. Explicit Instruction (EI) method is designed to support student learning process with declarative and procedural knowledge which is structured with gradual, step by step activity pattern. Model EI is demonstrated and practicum. This research is aimed to apply Explicit Instruction learning in Graphic Design and Animation course. In addition to know the interaction of the application of learning methods to learning achievement. This type of research is Classroom Action Research (PTK) which is implemented in two cycles. Each cycle consists of four stages: planning, execution, observation and reflection. The subjects of the study were four semester students who took the course of Graphic Design and Animation Off B for 45 students. The results showed that the application of EI learning model can improve learning outcomes. From the results of the action cycle I obtained data with an average value of 66. While in the second cycle mengingkat obtained mask with an average value of 80. From the results showed that the application of EI learning model in the course Graphic Design and Animation can improve learning outcomes.